Caso de estudio: empresa CBRE - Chuquiyauri Bautista, Diana Jazmín (2022)
The objective of this work is to analyze the company CBRE, we will see what strategies it uses and we will analyze its strengths and weaknesses, with the purpose of improving our approaches and capabilities according to the business model that is managed. In the same way, we will study the internal and external environment in which it is surrounded, we will compare its situation with other competing companies and we will find out what are the substitute products that could put its development in the Peruvian market at risk. In addition, we will analyze the most outstanding matrices in order to determine if the current objectives are enough to achieve the strategy or if it will be necessary to rethink objectives and implement and reformulate them to achieve exponential growth. CBRE is a well-structured company and has been in business for years. Currently it has loyal target audience and, in this work, we will know what competitive advantages it uses to stand out from the rest and what it does to keep them satisfied.